Nutritional and Bioactive Aspects in Functional Food Development - Marsa; Nisya Nadira Putri (Professorline, 2026)
Functional foods are designed to provide health benefits beyond basic nutrition by combining essential nutrients with bioactive compounds such as antioxidants, polyphenols, probiotics, prebiotics, and omega 3 fatty acids. These bioactive compounds help regulate physiological functions by reducing oxidative stress, modulating inflammation, improving gut microbiota balance, supporting immune response, and lowering the risk of chronic diseases such as cardiovascular disease, diabetes, and certain cancers. The development of functional foods requires careful selection of raw materials that are naturally rich in nutrients and bioactive compounds. Processing techniques such as fermentation, encapsulation, controlled heating, and drying play a critical role in maintaining bioactive stability, enhancing bioavailability, and ensuring sensory quality. Furthermore, interactions between nutrients and bioactive compounds must be considered to optimize health benefits without compromising taste, texture, or safety. Overall, functional food development is a multidisciplinary approach that combines nutrition science, food chemistry, and biotechnology. By integrating evidence-based formulations, manufacturers can produce foods that not only meet dietary needs but also actively promote health, prevent disease, and improve overall quality of life.